Pengaruh Promosi Dan Harga Terhadap Keputusan Pembelian Honda Beat Pada PT Tunas Honda Natar - Danang Fahrozi; Susi Indriyani; Prima Rini; Evi Meidasari (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine the influence of promotions and prices on purchasing decisions for Honda Beat at PT Tunas Honda Natar. The data used in this research is primary data, namely data collected by the researcher himself directly from the first source or place where the research object was carried out, namely the results of interviews and questionnaires distributed to consumers at PT Tunas Honda Natar. As well as secondary data, namely data collected from other parties, namely books, articles and journals related to this research. The analysis techniques used are validity and reliability tests, classical assumption tests, hypothesis tests, coefficient of determination (R2), and multiple linear regression tests. Based on the results of the analysis, it can be concluded that partially Promotion and Price have a significant effect on Purchasing Decisions and simultaneously Promotion and Price have a significant effect on Purchasing Decisions.